Executive function deficits associated with anxiety and depression and their impact on medical students’ academic performance in Saudi Arabia - Alfakeh, Sulhi A.; Alharbi, Alya S.; Alhebshi, Mohammed K.; Attar, Abdullah F. (Journal of Contemporary Medical Sciences, 2022)
Objectives: This study aimed to determine the relationship between EF deficits associated with anxiety and depression and their impact on medical students’ academic achievement in Saudi universities. Methods: A cross-sectional online survey was conducted on 242 medical students. Anxiety and depression were assessed using the Barkley Deficits in Executive Functioning Scale (BDEFS), General Anxiety Disorder-7 scale (GAD-7), and the Patient Health Questionnaire (PHQ-9). Results: Participants’ mean age was 22.57 (2.26) years and the mean GAD-7, PHQ-9, and BDEFS scores were 10.54 (5.83), 12.29 (6.86), and 196.78 (47.78), respectively. Males, Saudi students, those in their fourth academic year, and those who were not satisfied with their academic performance had significantly higher mean GAD-7, PHQ-9, and BDEFS scores. A significant negative association was found between students’ grade point average (GPA) and BDEFS scores, and a significant positive association was found between GPA and GAD-7 scale scores, PHQ-9 scores, and BDEFS scores. Additionally, there was a positive association between the PHQ-9 and BDEFS scores. Conclusion: A real-world application of EF scales to address EF deficits for all university students should be considered.